2011
DOI: 10.1167/iovs.11-7758
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Blood Flow Response to Isometric Exercise in Glaucoma Patients and Patients with Ocular Hypertension

Abstract: Baseline ChBF was lower in both the POAG and the OHT patients, compared with that in the controls. The stronger increase in ChBF in POAG patients in the face of an exercise-induced blood pressure increase indicates less active regulatory capacity in glaucoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 35 publications
(45 reference statements)
1
40
0
Order By: Relevance
“…Choroidal, retinal, and ONH blood flow have been found to be reduced in patients with glaucoma compared with healthy controls. [28][29][30] In addition, also autoregulation of ocular blood flow appears to be disturbed in this group of patients. [30][31][32] Autoregulation is defined as the capability of a vascular bed to keep its blood flow constant despite changes in OPP.…”
Section: Pathophysiology Of Glaucomamentioning
confidence: 81%
See 1 more Smart Citation
“…Choroidal, retinal, and ONH blood flow have been found to be reduced in patients with glaucoma compared with healthy controls. [28][29][30] In addition, also autoregulation of ocular blood flow appears to be disturbed in this group of patients. [30][31][32] Autoregulation is defined as the capability of a vascular bed to keep its blood flow constant despite changes in OPP.…”
Section: Pathophysiology Of Glaucomamentioning
confidence: 81%
“…[28][29][30] In addition, also autoregulation of ocular blood flow appears to be disturbed in this group of patients. [30][31][32] Autoregulation is defined as the capability of a vascular bed to keep its blood flow constant despite changes in OPP. 33 Large-scale studies also found low OPP, which can be estimated as the difference between mean arterial blood pressure and IOP, as a risk factor for the onset and progression of glaucoma.…”
Section: Pathophysiology Of Glaucomamentioning
confidence: 81%
“…[5][6][7][8][9][10][11][12][13][14][15][16] Alterations of the response in ChBF have been observed in smokers 17 and vasospastics, 18 as was well as in patients with diabetic retinopathy, 19 central serous chorioretinopathy, 20 agerelated macular degeneration, 21 and glaucoma. 22 By contrast only few studies have investigated optic nerve head blood flow (ONHBF) during changes in OPP. [23][24][25][26][27][28] The aim of our study was to extend our understanding of ONHBF regulation during changes in OPP.…”
Section: Discussionmentioning
confidence: 99%
“…3 These unstable vascular abnormalities might also affect ocular blood flow, which can be assessed using color duplex imaging, laser speckle method, or Doppler flowmetry. 4,5 However, because the choroid receives approximately 95% of all ocular blood flow, changes in its structure could help to evaluate choroidal, thus ocular blood flow. 6 In several recent studies, optical coherence tomography (OCT) was introduced as an effective tool for evaluating choroidal thickness.…”
Section: Introductionmentioning
confidence: 99%